New genus and two new species of American Desmiphorini (Coleoptera, Cerambycidae, Lamiinae) - Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2017)
Rosalbopsis wappesi, a new species belonging to a new genus of Desmiphorini, is described from Panama. Eupogonius obrienorum sp. nov. is described from Mexico.